Wellness integrated information system / Leong Weng Liong - Leong , Weng Liong (2004)
Wellness Integrated Information System is a web-based system with an integrated database developed especially for the used of University of Malaya Total Wellness Programme. Wellness Integrated Information System is designed to create an information rich environment of wellness resources, that is accessible and available. The users of the system are categorized into 4 main groups, namely, the Wellness Administrator, Committee Members, Participants and Visitors. The Wellness Integrated Information System includes 6 modules that are Login and Logout, Question & Answer Board, Information Resources, Search Help and Notice Board Module. The users of the system will be allowed different access level. Only authorized users will be allowed to create, maintain and make changes, delete or update the database under their respective scope . In order to ensure authorized access to the system, user's login and password validation will be required. The development methodology selected in building this system is the Waterfall Model with Prototyping. Wellness Integrated Information System is developed using open source. Thus the development tools include PHP ( Hypertext Preprocessor) as the system's server side scripting language MySQL as the database and Apache as the web server. The combination of PHP and MySQL together with Apache server on a three-tier architecture is guaranteed to optimize performance. Besides that, Microsoft Internet Explorer 6.0 will be used as the web browser and Windows 2000 as the operating system. Interface development tools used are Macromedia Dreamweaver MX 6.0, Microsoft Frontpage and Adobe Photoshop 6.0.